Thinking through work: complex inequalities, constructions of difference and trans-national migrants - McDowell, L (SAGE Publications, 2008)
This paper raises questions - rather than providing answers - about the theorization of intersectionality: the complex inequalities that result from connections between gender, class, ethnicity and other dimensions of identity in the making of subjects. I draw on Ong's work on cultural citizenship and notions of subjectification from Foucault and Butler to think through feminist theorizations of intersectionality and the philosophical status of different approaches to complexity and difference. I also address methodological issues. While this is not primarily an empirical paper, I use the example of the labour market position of recent migrants into the UK as an examplar of intersectionality at work.